2015
DOI: 10.2147/por.s64973
|View full text |Cite
|
Sign up to set email alerts
|

Remission, response, and relapse rates in patients with acute schizophrenia treated with olanzapine monotherapy or other atypical antipsychotic monotherapy: 12-month prospective observational study

Abstract: PurposeTo compare the rates of antipsychotic response, remission, and relapse in patients with schizophrenia treated with olanzapine or other antipsychotics in usual clinical care in Japan.Patients and methodsThis analysis of a 12-month, prospective, noninterventional study examined outcomes for 1,089 inpatients and outpatients with schizophrenia who initiated antipsychotic monotherapy. All treatment decisions, including medication choice, were left to the discretion of the treating physician. The rates of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…7,8 In studies comparing the long-term effectiveness of several antipsychotic medications, treatment with olanzapine resulted in lower rates of hospitalization for disease exacerbation 8,9 and higher rates of remission. 10,11 Time to all-cause discontinuation was also consistently longer for olanzapine compared with other antipsychotics across multiple studies. [7][8][9]12,13 Despite its established efficacy, olanzapine is associated with a risk of significant weight gain, 8,14,15 which has limited its overall clinical utility.…”
Section: Introductionmentioning
confidence: 98%
“…7,8 In studies comparing the long-term effectiveness of several antipsychotic medications, treatment with olanzapine resulted in lower rates of hospitalization for disease exacerbation 8,9 and higher rates of remission. 10,11 Time to all-cause discontinuation was also consistently longer for olanzapine compared with other antipsychotics across multiple studies. [7][8][9]12,13 Despite its established efficacy, olanzapine is associated with a risk of significant weight gain, 8,14,15 which has limited its overall clinical utility.…”
Section: Introductionmentioning
confidence: 98%
“…13,14 Despite a number of available antipsychotics, there remains a need for effective therapies with acceptable tolerability profiles that support long-term use. [15][16][17] Based on data from clinical trials, 18,19 real-world settings, [20][21][22] meta-analyses, 23,24 and pooled analyses, 25 olanzapine is one of the most effective antipsychotics for the treatment of schizophrenia. 26,27 Olanzapine also effectively treats manic or mixed episodes associated with BD-I and reduces relapse risk during maintenance treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Making the patient had lower quality of life, self-care ability, high economic burden on the family and society, and progressively chronic disease. [13][14][15] Besides, misconceptions, negative perceptions, caregivers' attitudes about schizophrenia created barriers in compliance with rehabilitation for the people. 10,[16][17] From literature review, research results indicated that there were various factors associated with caregiver's schizophrenic rehabilitation compliance.…”
mentioning
confidence: 99%